Medical AM of High Performance Plastics at the Point-of-Care (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: 3D-Printing will be a technology that shapes the future of medical production. The way how we are creating medical products, like implants or surgical guides, can be lasting influenced. 3D-prinitng allows the production of individualized medical products in a sustainable way and can create real patient value. In the latest time a lot of hype is around 3d-printing in hospitals, so point-of-care medical production.Materials and Methods: In this presentation the challenges and advantages of point-of-care printing with high performance polymers should be valued. Furthermore, the technology of Kumovis, based on FLM-technology should be presented and clinical use cases should be shown. Regulatory aspects as well as the technical equipment will be discussed in the context of on-site-printing.Results and Discussion: Main challenges are the usability, biocompatible materials and outcome, process monitoring as well as process validation. Kumovis developed a 3D-printer specialized for the medical sector. The heart of the technology is the patented temperature control. The build-plate is surrounded by a laminar air stream, that can be heated up to 250°C. So, a homogenous temperature distribution inside the build chamber can be ensured, what is necessary for high quality printing at high reproducibility. Furthermore, it is possible to include filter techniques to ensure an environment without particles. We will present first clinical applications in the dental area as well as a solution for a lower jaw reconstruction with 3D-printing.Conclusion: With the right combination of software and hardware, 3D-printing will be the technology that shapes the production of medical products. Products like surgical guides, impression trays or applications in the dental area will be possible to be printed directly at the point of care. A main challenge will be the regulatory aspect. Especially for higher class medical products the collaboration with established medical producers can a good solution.